DEVELOPING SCIENTIFIC-TECHNICAL AND CREATIVE ABILITIES IN SCHOOL-AGE CHILDREN - Makhmudova Sarvinoz Samar kizi (Scholar Express Journal, 2024)
This article discusses fostering the curiosity for entrepreneurship in school-age children, enhancing their scientific proficiency, and the effectiveness of time management and the correlation between pedagogy and scientific-technical skills. In this article, also guidelines are provided for tasks that need to be started from the moment of each child's birth. Our brighter future begins with intelligent and capable children
Keywords: Mind-stimulating toys; efficiency from gadgets; pomodoro technique; effective sleep schedules